Preventing, Controlling, and Sharing Data of Arsenicosis in China - Yuanqing Tong (Data Science Journal, 2007)
The first case of arsenicosis was reported in China in the 1950s. That incident was associated with the so-called "black foot disease." In the late 1970s and early 1980s, arsenic specific coetaneous changes were diagnosed in the Xinjiang Autonomous Rregion and subsequently in the Inner Mongolia Autonomous Region and Shanxi Province. Recently, endemic arsenicosis was also found in Jilin, Ningxia, Qinghai, and Anhui Provinces. The prevalence of arsenicosis in China is becoming more and more serious. In order to prevent and control it, many departments and institutes have begun to work in this field. They have made a great progress including also the sharing of arsenicosis data within a limited area. But the limited nature of this data sharing is a barrier for preventing and controlling arsenicosis. Only once data sharing is realized within the whole nation, can we discover the best way of eliminating arsenicosis. With this goal in mind, we have set up a rudimentary platform of asenicosis data sharing. This gradually needs to be improved and improved.